Institucionalização das práticas de atenção às condições crônicas e os processos de trabalho em um serviço de atenção primária - Silocchi, Cassiane (Universidade do Vale do Rio dos Sinos, 2019)
This study aimed at analyzing the institutionalization of practices of attention to chronic conditions on work processes in the Community Health Service of the Hospitalar Conceição Group of Porto Alegre (RS), in order to identify the instituted and instituting dynamics and the "critical nodes" that may be hindering or enhancing work processes. The chosen theoretical-methodological reference was the Institutional Analysis, in its socioanalytical aspect. The tools used in this intervention research were Participant Observation, the holding of Groups with health teams and semi-structured interviews with those responsible for research development and evaluation of group services. The results showed tension between the traditional model and the resistance of the subjects in face of the new modes of care; the lack of involvement of professionals, pointing to conflicts between the individual fulfillment of tasks and collective engagement and, finally, a tension between the goals required, based on productivity and the incorporation of innovative interventions.
Keywords: Análise Institucional; Doença crônica; Processo de trabalho; Atenção primária à saúde; Institutional analysis; Chronic disease; Work process; Primary health care; ACCNPQ::Ciências da Saúde::Saúde Coletiva